Blurring the shoreline: De- and re-infrastructuring and the changing colors of European flood policy. (June 2021) - Petersson, Jesper
This paper provides a genealogy of the emergence of a common EU flood policy, including the scope and direction of this policy. Noticing how EU policy proposes green infrastructure (associated with using nature as a buffer zone in managing floods) as an alternative to grey infrastructure (implying fixed installations of concrete and cement), this paper adopts the theoretical lens of the so-called infrastructural turn, which advocates a relational investigation of infrastructure. By engaging this approach, the paper shows how flood infrastructure can contain very different compositions of (unruly) water and (settled) land. A narrative of a historically strong focus on guarding society from the powerful forces of nature through a fixed line of defense is increasingly giving way to more muddy states—quite literally—where society is expected to learn to live with flooding and show ecological consideration. To capture the EU's, and especially the European Commission's efforts to establish a pan-European flood infrastructure that accommodates this turn, the concepts of de- and re-infrastructuring are developed. These concepts act as heuristic devices to capture how policy performs some combinations between water and land as constituting an attractive and functional flood infrastructure, but constitutes other infrastructural relations of the aquatic and the terrestrial as undesirable and, hence, as malfunctioning. This performative act of distinguishing between what constitutes "good and proper" versus "bad and undesirable" infrastructure is referred to as a politics of infrastructure.